Karyotipe characterization of eight mexican species off Eleocharis (Cyperaceae) - Tena Flores, J.A.=700 1 Gonzalez Elizondo, M.S.; Herrera Arrieta, Y.; Almaraz Abarca, M.; Mayek Perez, N.; Maximiano Da Silva, C.R.; Laforga Vanzela, A.L.
(Es, En)
Ilus., 61 ref.
Keywords: ELEOCHARIS; CIPERACEAE; CITOTAXONOMIA; CROMOSOMAS; DIPLOIDIA; MEXICO; HOLOCENTRICO